Implementasi Pendidikan Idealisme di Perguruan Tinggi Swasta STAI Raudhatul Akmal Batang Kuis Deli Serdang - Masyitah Masyitah; Wildansyah Lubis; Yacobus Ndona (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Idealism in education is an approach that emphasizes the holistic development of individual potential, encompassing intellectual, moral, and social aspects. STAI Raudhatul Akmal, as a private institution, envisions producing graduates who are not only academically competent but also possess integrity and the ability to face societal challenges. This study aims to identify and analyze the implementation of idealistic educational principles in the curriculum and learning practices at STAI Raudhatul Akmal. A qualitative approach was employed, with data collected through interviews, observations, and document analysis. The findings indicate that integrating idealistic values is evident in teaching, where lecturers act as facilitators, encouraging students to think critically and creatively.Additionally, extracurricular activities based on ethical and moral values shape student character. This research recommends enhanced training for lecturers and developing more structured programs to ensure that idealism values can be internalized more effectively. Thus, it is hoped that graduates of STAI Raudhatul Akmal can become positive agents of change in society, which aligns with the goals of idealism education.